The CD300c antibody CL7 suppresses tumor growth by regulating the tumor microenvironment in non-small cell lung carcinoma - Kim, Soyoung; Han, Ik-Hwan; Lee, Suin; Park, Sujin; Jeon, Jae-Won; Bae, Hyunsu (Frontiers in Oncology, 2025)
Despite advances in therapy, non-small cell lung cancer (NSCLC) continues to rank among the deadliest cancers worldwide. Targeting immunosuppressive components within the tumor microenvironment (TME) has emerged as a promising therapeutic strategy. Unlike M1 tumor-associated macrophages (TAMs), M2-like TAMs contribute to NSCLC progression by promoting an immunosuppressive tumor microenvironment (TME), highlighting the need for tumor microenvironment remodeling. CL7, a monoclonal antibody that targets the activating receptor CD300c on human monocytes and macrophages, was selected as a therapeutic candidate because CD300c engagement triggers MAPK and NF-κB signaling pathways, promoting M1 macrophage polarization and antitumor immune activation. To evaluate the therapeutic potential of CL7, we established an orthotopic NSCLC model by inoculating LLC-luc cells into the left lung of mice. We administered CL7 intraperitoneally at doses of 5 or 10 mg/kg twice a week. Only representative data from the 10 mg/kg CL7 group are shown to maintain consistency with subsequent analyses (flow cytometry, RT-qPCR, and IHC). Tumor growth was significantly suppressed in the CL7-treated group compared to the PBS control group. CL7 treatment also modulated the tumor microenvironment by increasing the population of M1 macrophages and CD8+ T cells, while decreasing the population of regulatory T cells. Our findings suggest that CL7 exerts antitumor effects in NSCLC by reprogramming the immunosuppressive landscape of the TME and enhancing antitumor immunity.